Cultura de anteras e de embriões zigóticos imaturos no melhoramento de pimenteiras ornamentais (Capsicum annuum L.) - Barroso, Priscila Alves (2016)
The pepper cultivates in pots have stood out in the ornamental market for its aesthetic features that include, among other attributes, the fruits and leaves color and harmony with the pots. The ornamental pepper breeding has been carried out over the long-term, involving multiple cycles of selfing. Biotechnological techniques, such as the culture of anther and immature zygotic embryos, can assist breeding programs reducing the time for the release of new cultivars. Thus, the objective was to induce androgenics embryos from anthers of different genotypes of ornamental pepper and regenerate viable plants from in vitro culture of immature zygotic embryos in different genotypes of ornamental pepper (Capsicum annuum L.). For anther culture technique were used anther of nine parents and five hybrids. These were maintained at 4°C for 3 days and subsequently cultured in double layer, with and without growth regulator and maintained in B.O.D. at 9 ° C for one week and then at 28° C in the absence of light. The cultivation of zygotic embryos, fruit of three genotypes were collected 20, 25, 30 and 35 days after selfing (DAA). Fruits were characterized and determined the embryo stage of development. The embryos were inoculated in the petri dishes containing the media: ½ MS and MS overall strength. It was recorded the number of embryos germinated and losses during acclimatization and transplantation, also the characterization of seedlings and plants in a greenhouse. In addition, it was determined breeding cycle plant of immature embryos and by the conventional method. There was influence of the media and genotypes in the induction of androgenic embryos. Fully developed embryos were observed in genotypes UFPB 001, UFPB 004 and UFPB 099 but a lot of abnormal embryos was recorded. Zygotic embryos at different developmental stages can be found in the same fruit characterizing the asynchronous development. Lower rates of germination and development of seedlings were observed in earlier fruit, being observed also influences the genotype. The interaction between the periods, genotypes and media influenced the morphological characterization of the plants in the greenhouse. On average a reduction of 30% was observed in the breeding cycle in the three genotypes. Further studies should be conducted to increase the conversion of normal androgenic embryos and in the case of zygotic embryos, increase germination rates in periods of 20 and 25 DAA and reduce losses during acclimatization and transplantation. Still, a considerable reduction in cycle improvement was achieved as well as the identification of genotypes responsive to anther culture. Thus, it will be a valuable tool for ornamental breeding program.